2019
DOI: 10.3390/ijms20215300
|View full text |Cite
|
Sign up to set email alerts
|

USP14 Inhibition Regulates Tumorigenesis by Inducing Autophagy in Lung Cancer In Vitro

Abstract: The ubiquitin–proteasome system is an essential regulator of several cellular pathways involving oncogenes. Deubiquitination negatively regulates target proteins or substrates linked to both hereditary and sporadic forms of cancer. The deubiquitinating enzyme ubiquitin-specific protease 14 (USP14) is associated with proteasomes where it trims the ubiquitin chain on the substrate. Here, we found that USP14 is highly expressed in patients with lung cancer. We also demonstrated that USP14 inhibitors (IU1-47 and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…It has also been reported that IU1-47 causes a degradation of wild-type tau in neurons at a significantly higher rate than IU1 due to its extra targets on lysine-174 in tau protein, which may contribute to the higher specificity and efficacy [227]. A recent study has tested IU1-47 in lung cancer and proved that the inhibition of proteasome USP14 by IU1-47 could significantly decrease cell proliferation, migration, and invasion in lung cancer [130].…”
Section: Inhibitors Of 19s Proteasome Regulatory Particlesmentioning
confidence: 99%
“…It has also been reported that IU1-47 causes a degradation of wild-type tau in neurons at a significantly higher rate than IU1 due to its extra targets on lysine-174 in tau protein, which may contribute to the higher specificity and efficacy [227]. A recent study has tested IU1-47 in lung cancer and proved that the inhibition of proteasome USP14 by IU1-47 could significantly decrease cell proliferation, migration, and invasion in lung cancer [130].…”
Section: Inhibitors Of 19s Proteasome Regulatory Particlesmentioning
confidence: 99%
“…Though USP14 is more pronounced for its therapeutic potential in cancer (Shinji et al, 2006;Liao et al, 2018;Han et al, 2019), its role in neurodegenerative disorders is also known (Boselli et al, 2017;Min et al, 2017;Chakraborty et al, 2018). It is well accepted that the influence of USP14 on proteasome complex activity is inversely correlated (Lee et al, 2010;Kim and Goldberg, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, tests using IU1 in animal models have yielded mixed results. Consistent with promotion of proteasomal degradation of damaged proteins by USP14 inhibition, IU1 and exosomal miR124, both suppress USP14, were shown to protect against cerebral ischemia/reperfusion injury in mice [23,24], but USP14 inhibition was also shown to induce cell death and effectively treat malignancies in animal models [25,26]. Moreover, the axJ mouse that is homozygous for an apparently loss-of-function mutation of Usp14 and with a reduction of USP14 protein by 95%, shows severe neuromuscular abnormalities at 2-3 weeks and dies between 6-10 weeks of age [27].…”
mentioning
confidence: 79%